Holy war - Armstrong, Karen, 1944- (New York)
xviii, 628 sayfa, [6] harita
Keywords: “Karen Armstrong, bestselling author of A History of God, skillfully narrates this history of the Crusades with a view toward their profound and continuing in-fluence. In 1095 Pope Urban II summoned Christian warriors to take up the cross and reconquer the Holy Land. Thus began the holy wars that would focus the power of Europe against a common enemy and become the stuff of romantic legend. In reality the Crusades were a series of rabidly savage conflicts in the name of piety. And, as Armstrong shows in this fascinating book, their legacy of religious violence continues today in the Middle East, where the age-old conflict of Christians, Jews, and Muslims persists.” --